2013
DOI: 10.1111/his.12296
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of αGlcNAc in Barrett's oesophagus adjacent to Barrett's adenocarcinoma – a possible biomarker to predict the malignant potential of Barrett's oesophagus

Abstract: Reduced expression of αGlcNAc in Barrett's oesophagus adjacent to Barrett's adenocarcinoma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 51 publications
3
10
0
Order By: Relevance
“…In a previous study of tumours from gastric cancer patients, we showed that loss of αGlcNAc expression in MUC6‐positive differentiated‐type adenocarcinoma was significantly correlated with invasion, stage, venous invasion of tumour cells, and poor prognosis of the patients . In addition, we revealed that decreased αGlcNAc expression in BO predicts the potential for development of BAC . These earlier findings combined with those of the present study suggest that αGlcNAc is an important biomarker, not only for predicting gastric cancer prognosis, but also for estimating the malignant potential of BO and PGA.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In a previous study of tumours from gastric cancer patients, we showed that loss of αGlcNAc expression in MUC6‐positive differentiated‐type adenocarcinoma was significantly correlated with invasion, stage, venous invasion of tumour cells, and poor prognosis of the patients . In addition, we revealed that decreased αGlcNAc expression in BO predicts the potential for development of BAC . These earlier findings combined with those of the present study suggest that αGlcNAc is an important biomarker, not only for predicting gastric cancer prognosis, but also for estimating the malignant potential of BO and PGA.…”
Section: Discussionsupporting
confidence: 84%
“…8 More recently, we revealed that reduced aGlcNAc expression relative to MUC6 expression was associated with malignant potential of gastric differentiatedtype adenocarcinoma. 9 We also showed that aGlcNAc expression levels relative to MUC6 expression levels were reduced in Barrett's oesophagus (BO) adjacent to Barrett's adenocarcinoma (BAC) as compared with BO without BAC, 10 indicating that aGlcNAc loss occurs not only in cancer cells but also in adjacent non-cancerous cells. However, the relationship between aGlcNAc loss and tumorigenesis in PGA remained unknown.…”
Section: Introductionmentioning
confidence: 95%
“…Hence, α1–4GlcNAc on core 2 prevents gastric cancer through its antibiotic properties toward H. pylori and by preventing protumorigenic inflammation in the stomach. In line with these mouse studies, loss of α1–4GlcNAc has been observed in patients with gastric carcinoma and Barrett’s adenocarcinoma and found to correlate with worse survival in gastric cancer (Iwaya et al, 2014; Shiratsu, Higuchi, & Nakayama, 2014). …”
Section: Altered O-glycan Structures Observed In Cancersupporting
confidence: 61%
“…may be driving the development of dysplasia/carcinoma from metaplastic condition. In line with this, studies have shown differential expression of glycan structures in tissue and serum samples during metaplasia-dysplasia-carcinoma sequence (23,(31)(32)(33)(34)(35)(61)(62)(63)(64)(65) The lack of glycosylation changes between healthy and BE was somewhat surprising because genomic studies suggest that BE and EAC share a common mutational profile that differs from healthy samples (59,60). The top candidate that differentiated between healthy and BE, NPL-APOB, was influenced by BMI.…”
Section: Discussionmentioning
confidence: 70%